Ultrastructural Changes of Synapses in the Hippocampus of Sprague Dawley Rat Brain following Exposure to Naphthalene Balls - Angu Bala Ganesh Koduvai S. V; Soman Sharath; Reginald Sharon Roshin; Yadav Omnath P (Wolters Kluwer Medknow Publications, 2024)
IntroductionThe synaptic contacts play an important role in central nervous system (CNS) functioning. Ultrastructural features of synapses in CNS are not studied in naphthalene neurotoxicity model. Materials and MethodologyIn the present work, transmission electron microscopy was used for studying the ultrastructural features of synapses in the hippocampus of Sprague Dawley rat brain, on subsequent exposure to naphthalene balls. The ultrastructural changes were observed for naphthalene low dose (200 mg), high dose (400 mg) after the treatment for 28 days, and post-delayed toxicity phase after 14 days in Sprague Dawley rats. ResultsIn comparison with different groups of naphthalene exposure including control and satellite, axon degeneration, axonal demyelination and abnormal synapses was observed in high dose naphthalene administration group. In the post-delayed naphthalene toxicity group, degeneration of synaptic contacts was observed. ConclusionsThis exploration of ultrastructural variations in the synapses of Hippocampus gives information that will be valued in naphthalene neurotoxicological research.